Comparison of safety and efficacy of Oral Terbinafine with Amphotericin B gel and Sertaconazole cream for the treatment of Tinea Corporis and its effect on quality of life of patients - Sumedha Sirohi; Sumit Bhutani; Cherry Cheema; Gurleen Kaur; S P Singh; Prithpal S Matreja (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2017)
Background: Tinea Corporis is a superfi cial fungal infection affecting 20-25% of the world's population. Management involves using topical and oral antifungal drugs. Terbinafi ne has been used commonly for the treatment of tinea corporis to prevent the emergence of resistance combination of drugs is used. Hence, this study was designed to compare the safety and effi cacy of Sertaconazole and Amphotericin B when either is used with oral Terbinafi ne. Methodology: This open-label, randomized, prospective and parallel group study was conducted on patients suffering from tinea corporis visiting the Department of Dermatology. All patients underwent a thorough clinical examination to establish the diagnosis of tinea corporis and were divided into two groups. Patients in Group A received treatment with Sertaconazole and Terbinafi ne. Group B received treatment with Amphotericin B and Terbinafi ne. At the end of treatment phase patients were assessed clinically for the disease symptoms - erythema, pruritus, and scaling; adverse effects experienced and Dermatological life quality index (DLQI). Results: Fifty two (52) patients were enrolled in the study, both groups were comparable at baseline. After 2 weeks of treatment, complete clinical cure was found in 6 patients in Group A and 5 patients in Group B. The treatment also showed improvement in clinical disease activity as there was clinical improvement seen in 22 patients in group A as compared to 25 patients in Group B. Greater number of patients in Group B reported with symptomatic improvement. There was no serious adverse event reported in both groups and DLQI score was comparable. Conclusion: The use of topical antifungals along with systemic antifungals has been found to be useful in early achievement of clinical cure and improvement in clinical symptoms of tinea corporis.